2005
DOI: 10.1097/01.wnr.0000176515.11723.a2
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cerebellar vermal morphology and cognitive correlates in prenatal alcohol exposure

Abstract: Prenatal exposure to alcohol can result in neuroanatomical and neurocognitive deficits. High-resolution magnetic resonance imaging, surface-based image analytic methods, and neuropsychological measures were used to characterize the cerebellar vermis and to evaluate potential cognitive correlates of vermal morphology in 21 children and adolescents with prenatal alcohol exposure and 21 normally developing individuals. Alcohol-exposed individuals showed statistically significant reductions in the midline sagittal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 21 publications
8
96
2
1
Order By: Relevance
“…For example, a smaller caudate nucleus, a structure that is essential in learning and memory processing and storing [65], was found to strongly correlate with poor cognitive performance and verbal learning ability [66]. Poor verbal learning ability was also correlated with the amount of displacement of the corpus callosum [59] and the cerebellar vermis [49]. A thinner A C C E P T E D M A N U S C R I P T 10 dorsal frontal cortex was associated with poorer performance in verbal learning, while thinner frontal, parietal and temporal cortices were associated with better visuospatial functioning [39].…”
Section: Links Between Abnormal Brain Structures and Cognition In Fasdmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, a smaller caudate nucleus, a structure that is essential in learning and memory processing and storing [65], was found to strongly correlate with poor cognitive performance and verbal learning ability [66]. Poor verbal learning ability was also correlated with the amount of displacement of the corpus callosum [59] and the cerebellar vermis [49]. A thinner A C C E P T E D M A N U S C R I P T 10 dorsal frontal cortex was associated with poorer performance in verbal learning, while thinner frontal, parietal and temporal cortices were associated with better visuospatial functioning [39].…”
Section: Links Between Abnormal Brain Structures and Cognition In Fasdmentioning
confidence: 90%
“…In children and adolescents with FASD, large volume reductions were seen in the cerebrum [45], cerebellum ( Fig.3 [18]. Volume reduction and structural dysmorphology co-occurred in the case of the cerebellar vermis [49], but structural dysmorphology and asymmetry were present in the absence of volume changes in the case of the hippocampus and caudate nucleus [55;56]. Several studies reported wider cortical sulci [19;47;50].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In both nondysmorphic alcohol-exposed and FAS subjects, volume in the anterior cerebellar vermis (lobules I-V), an earlier developing part of the cerebellum, was significantly reduced after controlling for reduced brain size (Autti-Ramo et al, 2002;Sowell et al, 1996) while later developing regions were relatively spared Autti-Ramo et al, 2002;O'Hare et al, 2005). Analyses also revealed that the superior and anterior edges of the anterior vermis appear to be displaced in alcohol-exposed subjects as compared to controls (O'Hare et al, 2005). Participants with a diagnosis of FAS showed the greatest amount of displacement (1-3mm), while non-dysmorphic individuals with alcohol exposure histories showed less dramatic (1.4mm) alterations (O'Hare et al, 2005).…”
Section: Cerebellummentioning
confidence: 99%
“…In addition to reduced cerebellar volume, studies report damage localized to particular regions of the cerebellum (Autti-Ramo et al, 2002;O'Hare et al, 2005;Sowell et al, 1996). In both nondysmorphic alcohol-exposed and FAS subjects, volume in the anterior cerebellar vermis (lobules I-V), an earlier developing part of the cerebellum, was significantly reduced after controlling for reduced brain size (Autti-Ramo et al, 2002;Sowell et al, 1996) while later developing regions were relatively spared Autti-Ramo et al, 2002;O'Hare et al, 2005). Analyses also revealed that the superior and anterior edges of the anterior vermis appear to be displaced in alcohol-exposed subjects as compared to controls (O'Hare et al, 2005).…”
Section: Cerebellummentioning
confidence: 99%
“…Additional differences in hippocampal architecture between children with PAE and controls were found by Riikonen et al (1999Riikonen et al ( , 2005, who reported reduced hippocampal volumes and greater hippocampal asymmetry (i.e., left smaller than right) in children with PAE relative to controls, as well as by Autti-Rämö et al (2002), who found left hippocampal thinning in three children with varying levels of PAE. Several studies of PAE in children have used structural MRI to investigate the structure-function correlations between verbal learning and recall and the corpus callosum (Sowell et al, 2001), cerebellum (O'Hare et al, 2005), as well as overall cortical thickness (Sowell et al, 2008). No study, however, has directly examined whether the deficits in verbal learning and verbal and spatial recall in this clinical population are directly related to abnormalities in hippocampal development.…”
Section: Introductionmentioning
confidence: 99%